2017
DOI: 10.1371/journal.pone.0186302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical pharmacist interventions on inappropriate prophylactic acid suppressant use in hepatobiliary surgical patients undergoing elective operations

Abstract: ObjectiveTo evaluate the impact and cost-benefit of clinical pharmacist interventions on inappropriate use of prophylactic acid suppressant in hepatobiliary surgical patients in a Chinese tertiary hospital.MethodsA retro-prospective intervention study of patients undergoing elective operations was performed in the Department of Hepatobiliary Surgery of the Affiliated Hospital of Southwest Medical University. Patients admitted from October to December 2015 and from October to December 2016, served as the pre-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
1
21
0
7
Order By: Relevance
“…Another study showed that off-label drug use was found in 25 out of 36 clinical departments in a tertiary hospital in China [17] launched. Our previous study has confirmed that the clinical pharmacist's real-time interventions facilitated the rational use of prophylactic acid suppressant and resulted in favorable economic outcomes [19]. However, considering the current increase in the number of beds and the serious shortage of clinical pharmacists in our hospital, we decided to implement simple administrative intervention from January 1, 2018 to December 31, 2018 in present study in order to decrease the inappropriate use of Lipo-PGE 1 and to reduce Lipo-PGE 1 costs.…”
Section: Introductionmentioning
confidence: 63%
“…Another study showed that off-label drug use was found in 25 out of 36 clinical departments in a tertiary hospital in China [17] launched. Our previous study has confirmed that the clinical pharmacist's real-time interventions facilitated the rational use of prophylactic acid suppressant and resulted in favorable economic outcomes [19]. However, considering the current increase in the number of beds and the serious shortage of clinical pharmacists in our hospital, we decided to implement simple administrative intervention from January 1, 2018 to December 31, 2018 in present study in order to decrease the inappropriate use of Lipo-PGE 1 and to reduce Lipo-PGE 1 costs.…”
Section: Introductionmentioning
confidence: 63%
“…Another approach to reach improved outcomes in patient care within the perioperative area is the expansion of collaborative practice agreements (CPAs). CPAs between surgeons and pharmacists have demonstrated improved medication management and safety in multiple perioperative settings . These agreements often allow the PCPh to assess, review, and modify drug therapy independently, allowing the pharmacist to practice at the highest level within licensure.…”
Section: Conclusion and Future Of Perioperative Clinical Pharmacymentioning
confidence: 99%
“…These agreements often allow the PCPh to assess, review, and modify drug therapy independently, allowing the pharmacist to practice at the highest level within licensure. Examples of potential targets for CPAs may include the management of pain, delirium, gastric acid secretion, antimicrobial prophylaxis, blood glucose, and anticoagulation based on previously reported outcomes …”
Section: Conclusion and Future Of Perioperative Clinical Pharmacymentioning
confidence: 99%
See 2 more Smart Citations